The cultivation of Ulva lactuca (chlorophyta) in an integrated aquaculture system, for the production of abalone feed and the bioremediation of aquaculture effluent - Robertson-Andersson, Deborah (Department of Biological Sciences, 2014)
Includes bibliographical references (leaves 234-254).